2010
DOI: 10.12968/bjon.2010.19.sup8.79063
|View full text |Cite
|
Sign up to set email alerts
|

RCT of urethral versus suprapubic catheterization

Abstract: The use of intermittent catheterization following urogynaecological surgery is associated with a more rapid return to normal micturition and a shorter hospital stay, although the clinical significance of the difference is perhaps limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 11 publications
1
26
0
3
Order By: Relevance
“…Two trials received a score of 1 23,24 because the description of withdrawals was not deemed adequate. Adequate concealment was not the norm with only four trials 7,9,13,19 adequately concealing randomization. Half the trials adequately described their randomization process, and the majority described dropouts ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two trials received a score of 1 23,24 because the description of withdrawals was not deemed adequate. Adequate concealment was not the norm with only four trials 7,9,13,19 adequately concealing randomization. Half the trials adequately described their randomization process, and the majority described dropouts ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Intermittent urethral catheterization techniques (clean intermittent catheterization and clean intermittent self-catheterization) have demonstrated decreased rates of urinary tract infection when compared with indwelling urethral catheterization, 7,8 although increased nursing workload, cost, and varying patient preferences are factors that mitigate against opting for these newer forms of postoperative bladder drainage. 7,9,10 A recent Cochrane review examined options for short-term catheterization and concluded that further evidence was required before definite consensus could be reached. 11 However, the scope of the 2006 Cochrane was broad, including studies on both male and female populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3]10 Furthermore, three studies show advantages of CIC over SPC concerning acceptability, duration of treatment and hospitalisation. 23,25,26 The length of the prolongation period in the TIC group of 3 days might seem arbitrary. This period was chosen to reflect common practice in the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the findings of Dixon et al in their study. 4 Our interpretation is that women realise that they have a problem that needs to be managed. However, we also agree that the women's preferences need to be further explored and have done this by a patient preference study that evaluates in detail how women rate intervention-related bother.…”
Section: Authors' Replymentioning
confidence: 99%